2019
DOI: 10.1103/physrevlett.122.010406
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Hofstadter Interface

Abstract: Two-dimensional topological insulators possess conducting edge states at their boundary while being insulating in the bulk. The detection of edge states remains an open question in ultracold atom setups. We propose a configuration to implement a topological interface within the experimentally realizable time-reversal invariant Hofstadter model which gives rise to a topological phase boundary at the center of the system, and investigate the influence of two-body interactions on the interface in a fermionic syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 53 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Using the Dyson equation, these are used to construct a new lattice Green's function and this procedure is repeated until self-consistency. In 2d, DMFT has provided a successful description of topological systems for many aspects [30,[42][43][44][45][46][47][48]. Reference [49] showed that nonlocal contributions are small already in 2d.…”
Section: Interacting Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Dyson equation, these are used to construct a new lattice Green's function and this procedure is repeated until self-consistency. In 2d, DMFT has provided a successful description of topological systems for many aspects [30,[42][43][44][45][46][47][48]. Reference [49] showed that nonlocal contributions are small already in 2d.…”
Section: Interacting Phasesmentioning
confidence: 99%
“…For detection, Bloch-Zener-Stückelberg interferometry [61], anomalous velocity measurement, or state tomography [24] for bulk states as well as Bragg spectroscopy for surface states [15] have been proposed. Also a 3d version of a topological interface [46] could be used for the detection of the surface states. The local Z 2 marker introduced here could be used to distinguish the topological phase at the inter-face.…”
Section: Surface Statesmentioning
confidence: 99%
“…A second example is the topological interface [12,21,22] which is used to create an in-situ topological phase separation. In Fig.…”
Section: Interfacementioning
confidence: 99%
“…Since its introduction it enjoys great popularity in condensed matter theory as well as in the field of cold atomic gases. Applications range from heterojunctions [9] and quasicrystals [10] to interacting fermions [11] and interacting, spin-orbit coupled fermions at the smooth topological interface [12].…”
Section: Introductionmentioning
confidence: 99%
“…The local Chern marker provides an alternative tool for the calculation of an invariant in inhomogeneous systems. The local Chern marker has originally been introduced to capture aspects of topology in spatially inhomogeneous and/or finite systems [49] such as they arise in the presence of a trapping potential or interfaces (see, e.g., [50]). Here, we use the local Chern marker to obtain the global Chern number of our disordered systems by integration over the spatial coordinate.…”
Section: Introductionmentioning
confidence: 99%